Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Experience the convenience of getting reliable answers to your questions from a vast network of knowledgeable experts. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

If a(x + 1) + b(x − 1) − 2 = 0 for all real x, then a =
(A) -2
(B) -1
(C) 0
(D) 1
(E) 2


Sagot :

okiwix

Answer:

D) 1

Step-by-step explanation:

using the distributive property we have ax+a+bx-b-2=0. because the equation is true for all real x, ax=-bx. this means a-b-2=0 and a=-b. a-b-2=0 becomes a=b+2. then we substitute a for -b and get -b=b+2 which becomes 2b=-2 so b=-1. since a=-b, a=1